Pagamento municipal por serviço ambiental - proposição de um método de valoração monetária - (:unkn) unknown (Universidade Brasil, 2023)
In January 2021, Federal Law No. 14,119 was enacted in Brazil, which introduced the payment for environmental services. It determines that the parties involved may establish in agreement the amount and the payment method for the environmental service. The objective of this work is to propose a method of monetary valuation for payment for environmental services when provided by the individual, which should encourage the provision of environmental services by citizens, monetarily favoring effectiveness and efficiency aspects. For this purpose, through an applied, deductive, bibliographic study, with a qualitative and quantitative approach, of comparative and experimental nature, we focused on investigating monetary valuation for payment for environmental services that respond to the questions presented. As a result, the work proposed that a reference cost, discounting indirect costs and expenses, has to be calibrated through effectiveness and efficiency indices. Additionally, the result makes it possible to encourage the development of unstructured and diffuse economic chains to provide environmental services and social and economic development.
Keywords: Economia; Meio-ambiente; PSA; ASG; Sustentabilidade; Legislação Ambiental